Trud Stadium. History and prospects - Grigoryeva, Elena; Chertilov, Alexei (project baikal, 2025)
The article describes the history of the Stadium and Sports Palace Trud and characterises its purpose. The fate of mass sports in the city and the prospects for the existence of the Sports Centre Trud are considered.